THE DEVELOPMENT OF M-DIAGNOSTIC TEST TO IDENTIFY THE UNDERSTANDING LEVEL OF JUNIOR HIGH SCHOOL STUDENTS IN TEMPERATURE SUBJECT - Rusdianti, K; Linuwih, Suharto (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2017)
Abstract ___________________________________________________________________ The purpose of this research was develop a mobile phone diagnostic test product which use to identify student’s concept understanding in the temperature and heat material. This result indicated the level of student’s concept understanding in the temperature and heat material. This research has three steps for trial product. The steps were limited-scale, wide-scale, and implementation. The validation result by proffesional of instrument test, proffesional of media, and the questionnaire responses of students has been showed that the m-diagnostic test worthy to used because the product has fulfilled contents aspect, language aspect, construct aspect, software technology aspect, and visual communication aspect. The result of diagnostic test in implementation step are showed 6 students from 18 students that achieves a minimum completeness criteria.The result of student’s concept understanding that included in the relational understanding criteria for each indicator was 50% relational understanding for indicator 1 (knowing the definition of temperature and heat), 55% relational understanding for indicator 2 (understand the scale of the temperature on the thermometer. The results from this research indicated that the m-diagnostic test worthy to use for diagnose the level of student’s concept understanding.